"A Country of Hair": A Global Story of South Korean Wigs, Korean American Entrepreneurs, African American Hairstyles, and Cold War Industrialization. (16th June 2021) - PETRULIS, JASON
Abstract : This article reinterprets Asian industrialization during the Cold War through the lens of a forgotten commodity: the South Korean wig. Wigs were critical to Asia's "miraculous" economic growth—a US1 billion industry in 1970, as well as the number two export in South Korea and number four in Hong Kong at the height of export-oriented industrialization. The article makes a methodological argument, suggesting that we see industrialization differently when we "follow" a commodity transnationally—from the heads of rural South Koreans to the hands of Seoul factory workers to the shoulder bags of Korean American peddlers to the heads of African American women—and when we integrate bottom-up and top-down views of the commodity's "life." Only by taking this global perspective can we see how U.S. imperialism shaped the ways people and things moved across borders and oceans and how Cold War commodities were haunted by the lives of the people who touched them.